Supporting children with communication disorders : a handbook for teachers and teaching assistants - Thompson, Gill, active 2003-2005 (David Fulton Publishers, 2003)
This practical handbook provides SENCOs, class teachers and teaching assistants with a step-by-step guide to the identification of speech and language disorders, a basic knowledge of the underlying causes and guidance for developing strategies for support and intervention in the classroom. It gives a foundation for assessment and differentiation, which will help the teacher or teaching assistant to work effectively in collaboration with speech and language therapists. It suggests appropriate materials and programmes of work for enabling the child to access the curriculum as fu.